Pengembangan Media Pembelajaran Aplikasi BASAYA Learning untuk Meningkatkan Pemahaman Keberagaman Sosial Budaya pada Peserta Didik Kelas V - Sofi Fadillah Hendiyani; J. Julia; Rana Gustian Nugraha (Departement of Mathematics Education, 2023)
This development research aims to: (1) determine the process of developing the learning media for the BASAYA Learning application; (2) to know the effectiveness of the use of learning media in the BASAYA Learning application on Socio-Cultural Diversity material; and (3) knowing the level of practicality of learning media on students after using the BASAYA Learning application on Socio-Cultural Diversity material. The method used in this research is using the Design and Development (D&D) method and using the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The results of this study: (a) learning media products for the BASAYA Learning application are produced in the form of an .apk to be opened on a device (an Android-based application) and an .exe file to be opened on a Personal Computer (PC). (b) the products produced are